Lighthouse keepers - McKinty, Adrian (Amulet Books, 2008)
After teenage friends Jamie and Ramsay travel back to Altair to save the last citizens of that dying planet, the ancient race who built the mysterious, wormhole-seeking Salmon returns with a terrible proposition for Jamie.